Open source code for behavior analysis in rodents - Satoko Hattori; Yoshihiro Okumura; Keizo Takao; Yoko Yamaguchi; Tsuyoshi Miyakawa (Wiley, 2019)
Abstract Aim We have conducted a series of behavioral tests, which cover a broad range of behavioral domains, on various strains of genetically engineered mice. For the behavioral screening, we have been using Image J plugins that we developed for most of the tests in the battery. Our behavioral analysis system with the plugins enables systematic and automated image analysis of behavior. The plugins are freely available on the "Mouse Phenotype Database" website (http://www.mouse-phenotype.org/software.html). Here, we release the source code of the plugins in a Git repository with the aim of promoting their use and expanding their functionality. Methods We published the source code of the Image J plugins for behavioral analysis at Git repository (https://github.com/neuroinformatics). The source code for light/dark transition, elevated plus maze, open filed, T‐maze, and fear conditioning tests was made publicly available in the repository. Conclusions The source code of the plugins for the behavioral tests as well as the pre‐compiled binaries can be freely obtained. The open source code could promote the development and modification of the plugins for additional behavioral indices in these tests and for other behavioral tests.